Presentation-Based Learning and Peer Evaluation to Enhance Active Learning and Self-Confidence in the Financial Management Classroom (Malaysian Journal of Learning and Instruction, 2018)
Purpose â€“ The purpose of this study was to identify an effective learning strategy for students to engage authentically in their learning process. This study also aimed to introduce an innovative active learning approach to enhance studentsâ€™ involvement and to strengthen self-confidence throughout their learning in the Financial Management classroom. The approach involved the adoption of structured and accountable presentation-based learning activities. Methodology â€“ This study used action research design involving an iterative process of self-reflective cycles: planning, acting, observing and reflecting. The research was accomplished in two cycles. Three Financial Management classes of an undergraduate program consisting of 120 students in the first cycle and 110 students in the second cycle participated in this research as part of regular classroom activities. Semi-structured questionnaire, lecturer observation, and interviews were used as the method for data collection. The quantitative and qualitative data were analysed accordingly. Findings â€“ The results indicate that the approach adopted in this research reasonably enabled students to be actively engaged in their learning process and nullified free-riding learning behaviour among them.It also provided a chance for students to exercise their self regulated learning towards becoming more independent learners and increased their confidence to speak and participate in class Significance â€“ This research contributes to the improvement of teaching practices in higher education, particularly in Financial Management instruction. The results imply that providing some freedom for students to creatively design and be accountable for their own learning has great potential to enhance their authentic active learning and self-confidence.